Optimal performance of a combined heat-power system with a proton exchange membrane fuel cell using a developed marine predators algorithm. (15th February 2021) - Sun, Xianke; Wang, Gaoliang; Xu, Liuyang; Yuan, Honglei; Yousefi, Nasser
Abstract: This paper presents a micro Combined Cooling, Heating, and Power system coupled with a 5-kW Proton-Exchange Membrane Fuel Cell stack as primary mover to supply the households' requirements for cooling, heating and electricity. A new optimal methodology based on a modified bio-inspired optimization algorithm, called Developed Marine Predators Optimization Algorithm is introduced to improve the performance of the Combined Cooling, Heating, and Power system in terms of environment, thermodynamics, and economics. The reason for designing the developed version is to improve the algorithm efficiency in terms of accuracy, consistency, and convergence. The main idea is to maximize the economic performance and to minimize the annual cost of the Combined Cooling, Heating, and Power system during 20 years of life-span. For solving optimization problem, the proposed Developed Marine Predators Optimization Algorithm is used. After simulation, the results are compared with some other bio-inspired-based methods including NSGA-II and the basic Marine Predators Optimization Algorithm to indicate its higher efficiency. The results show that the maximum annual GHG reduction with 5.61e6 g belongs to the proposed DMPA with 52.6% exergy efficiency and 23.79e3 annual cost. The results also indicate that the final value of the exergy efficiency base on optimization is 32.57% that largely give better results comparing with the normal mode without optimization. Highlights: New approach for improving the effectiveness of a PEMFC-based CCHP system. Minimizing the annual cost of a CCHP system based on metaheuristics. Developed version of Marine Predators Optimization Algorithm based on DE's mutation operator and search mode. Comparison with NSGAII and the Basic MPO algorithm.